Ekstrak Daun Bandotan (Ageratum conyzoides lin) Memperbaiki Perilaku Depresi pada Mus Musculus - Melanie Ajeng Pratama; Muhammad Alim Jaya; Hanna Aulia Namirah; Ilma Khaerina Amaliyah Bakhtiar; Suci Noviyanah Ansary (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to assess immobility time in Sham group mice (Mus musculus), assess the effect of fluoxetine antidepressant on immobility time in mice (Mus musculus), assess the impact of bandotan leaf extract antidepressant (Ageratum conyzoides lin) on immobility time in mice (Mus musculus), evaluate the antidepressant effectiveness of the combination of bandotan leaf extract (Ageratum conyzoides lin) with fluoxetine on immobility time in mice (Mus musculus), and compare the efficacy of the four groups, namely group 1 (Sham), group 2 (fluoxetine), group 3 (bandotan leaf extract (Ageratum conyzoides lin)), and group 4 (Fluoxetine with bandotan leaf extract (Ageratum conyzoides lin)). This study uses a type of quantitative approach and pure experimental method (true experimental research) with Posttest only Control Group Design research design. The results showed that the mean immobility time in mice (Mus musculus) group 1 (Sham) was for 34 ± 22.1 seconds. The average immobility time in mice (Mus musculus) group 2 (Fluoxetine) is for 162.5 ± 44.43 seconds. The average immobility time in mice (Mus musculus) group 3 (Bandotan leaf extract) was 172.67 ± 40.5 seconds. The average immobility time in mice (Mus musculus) group 4 (Combination of fluoxetine with bandotan leaf extract) was 118.83 ± 24.1 seconds. The combination of fluoxetine with bandotan leaf extract has significance (p-value 0.039 <0.05) as an antidepressant in reducing immobility time in mice so that bandotan leaves can act as adjuvant therapy.